Women on a mission: Protestant legacies of gender equality in Africa? - Bastian Becker; Felix Meier zu Selhausen (African Economic History Network (AEHN), 2023)
Christian missions, especially Protestants missions, have been shown to advance longrun education outcomes and gender equality in Africa. However, the mechanisms behind this benign legacy and the contribution of missionary women, who constituted more than half of all Western mission staff, are not well-understood. We compile a new extensive data set on the locations of missions in colonial Africa, including the gender composition of their staff. In combination with contemporary survey data on one million respondents in 29 African countries, we provide evidence of missions' equalizing effects with regards to education and a wide range of female agency outcomes. We document that Protestant missions left no more benign legacy than Catholics, questioning the Protestant exceptionalism highlighted by prior studies. We also document a strong association between missionary women and girls' school enrollment in colonial times but find no evidence of any lasting gendered effects. Post-independence expansion of public education and the secularization of school curricula may have offset persistence of Africa's earliest centers of female education.
Keywords: 330; Christian Missions; education; Female Agency; Female Missionaries; gender